Laser Acupuncture: 35 Years of Successful Application in Russia (Narrative Review) - Moskvin, Sergey Vladimirovich; Agasarov, Lev Georgievich (Journal of Lasers in Medical Sciences, 2020)
Introduction: Laser acupuncture is one of the low-level laser therapy (LLLT) methods, replacing the traditional technique of Chinese needle acupuncture. This article describes the main principles and parameters of laser acupuncture based on the analysis of 35 years of successful experience in applying the method in Russia. Material and Methods: The search of the literature on laser acupuncture was made in the Russian Medical Library and the Russian State Library (1498 publications in Russian), and PubMed/ Medline (117 publications in English). 96 studies on laser acupuncture techniques were selected and a narrative review was conducted. Results: The optimal parameters of the technique were worked out by Russian specialists in the the1970s, and are perfectly confirmed by the wide practice of clinical application. The literature the review showed that the most optimal parameters of laser acupuncture are wavelength - 635 nm (red spectrum), power - no more than 2-3 mW, the diameter of special nozzle attachment - not more than 1-1.5 mm, and exposure - 20-40 s (for corporal points) or 5-10 s (for auricular points). The impact on acupuncture points (APs) is carried out consistently in accordance with the recipe (protocol), with no more than 10-12 daily procedures. Conclusion: Laser acupuncture is a very effective and reproducible technique to treat patients with different diseases. Any specialist can apply this method because of its simplicity, but using the most effective parameters.